Use of Plant Proteins as Microencapsulating Agents of Bioactive Compounds Extracted from Annatto Seeds (Bixa orellana L.) (2020)
ABSTRACT: This study aimed to assess the thermal stability of the bioactive compounds from annatto seed extract, encapsulated by ionic gelation using quinoa proteins, lentil proteins, soy proteins, and sodium caseinate as carrying materials. The 10.0% aqueous dispersions of the different proteins (carriers) were prepared and mixed with the annatto seed extract. The dispersions were then extruded into a calcium chloride solution to induce the extract encapsulation. The capsules were characterized by encapsulation efficiency, particle size, infrared transmission spectroscopy, confocal microscopy, and scanning electron microscopy (SEM). The antioxidant and antimicrobial activities, the polyphenol compounds, and bixin content from the free and encapsulated extract were assessed once stored for 12 d at different temperatures (4 ◦C, 25 ◦C, and 65 ◦C). The results demonstrated the ability of the proteins to encapsulate the annatto extract with encapsulation efficiencies ranging from 58% to 80%, where the protein structure and amino acid content were the relevant factors to obtain high encapsulation efficiencies. The free extracts stored at 65 ◦C for 12 d experienced a degradation of bixin and polyphenol compounds, respectively. Conversely, the encapsulated extract had degradations from ~34.00% to ~4.05% for polyphenol compounds and ~20.0% for bixin, respectively. These proteins have a potential encapsulation capacity of annatto extract by ionic gelation.